2008
DOI: 10.1667/rr1165.1
|View full text |Cite
|
Sign up to set email alerts
|

Repair of HZE-Particle-Induced DNA Double-Strand Breaks in Normal Human Fibroblasts

Abstract: DNA damage generated by high-energy and high-Z (HZE) particles is more skewed toward multiply damaged sites or clustered DNA damage than damage induced by low-linear energy transfer (LET) X and gamma rays. Clustered DNA damage includes abasic sites, base damages and single- (SSBs) and double-strand breaks (DSBs). This complex DNA damage is difficult to repair and may require coordinated recruitment of multiple DNA repair factors. As a consequence of the production of irreparable clustered lesions, a greater bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
94
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 44 publications
22
94
1
1
Order By: Relevance
“…Several studies suggest that residual damage, represented by a subset of DSB that cannot be quickly repaired or rejoined and persist for a longer time, is an indicator of the cell killing probability (1)(2)(3)(4)(5). This is qualitatively consistent with observations after high-LET radiation, where typically the yield of initially induced DSB is similar to that of photon radiation (6), but the fraction of residual damage is increased as compared to low-LET radiation, in line with the higher cell killing efficiency of high-LET radiation (7).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several studies suggest that residual damage, represented by a subset of DSB that cannot be quickly repaired or rejoined and persist for a longer time, is an indicator of the cell killing probability (1)(2)(3)(4)(5). This is qualitatively consistent with observations after high-LET radiation, where typically the yield of initially induced DSB is similar to that of photon radiation (6), but the fraction of residual damage is increased as compared to low-LET radiation, in line with the higher cell killing efficiency of high-LET radiation (7).…”
Section: Introductionsupporting
confidence: 84%
“…Several hypotheses have been discussed concerning the biological interpretation of these two components, and some of these suggest the presence of DNA damages of different severity, which are processed with different kinetics. This hypothesis is also in line with the slower rejoining observed after exposure to high-LET radiations compared to photons (7,(9)(10)(11).…”
Section: Introductionsupporting
confidence: 79%
“…At higher doses however (1 and 5Gy), a small dose-dependent number of residual persistent spots were detected. These observations are consistent with other reports on rejoining kinetics (34,35,45). It is plausible that the more persistent foci represent sites, where the repair machinery has difficulty repairing the breaks or where repair proceeds slower (46).…”
Section: Discussionsupporting
confidence: 92%
“…Previously we reported that Si ion-induced DNA damage was repaired in a manner similar to repair of γ-ray-induced damage and that a larger fraction of Fe ion-induced DNA damage was irreparable (11). The difficulties associated with repair of DNA lesions induced by irradiation with Fe ions may be due to either the number of complex DNA lesions produced or the nature of clustered lesions induced.…”
Section: Resultsmentioning
confidence: 99%